Time since menopause, but not age, is associated with increased risk of osteoporosis. (3rd September 2019) - Fistarol, M.; Rezende, C. R.; Figueiredo Campos, A. L.; Kakehasi, A. M.; Geber, S.
Abstract: Objectives: This study aimed to determine whether estrogen deficiency is a sole risk factor for osteoporosis or is also associated with age, through indicators such as gender, age, and time since menopause. Methods: A cross-sectional study was conducted evaluating 938 postmenopausal women who underwent bone mineral densitometry. We collected the following data: age, ethnic group, body mass index, smoking, and time since menopause. These data were correlated to the presence of osteoporosis, according to the T -score of the femur and lumbar spine. Results: The prevalence of osteoporosis was 37.8%. Ethnic group ( p = 0.47) and smoking habits ( p = 0.19) were not associated with osteoporosis. In the group of women with osteoporosis, mean age was significantly higher ( p < 0.001), mean body mass index was significantly lower ( p < 0.001), and time since menopause was significantly higher ( p < 0.001) than in the group of women with no osteoporosis. After multivariate analysis was performed, the only variables that remained independently associated with osteoporosis were body mass index and time since menopause. Higher body mass index was a protective factor (odds ratio = 0.80 [95% confidence interval 0.76; 0.84], p < 0.001). Time since menopause represented a risk factor for osteoporosis (odds ratio = 1.04 [1.02; 1.06], p < 0.001). When divided into categories, the risk increased after 20 years of menopause and gradually every 5 years. Conclusion: Time since menopause and body mass index were the most important factors associated with osteoporosis, confirming that estrogen deficiency, and not age, is the major cause of the disease.